Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1748-717x-9-93
|View full text |Cite
|
Sign up to set email alerts
|

Influence of body mass index and periprostatic fat on rectal dosimetry in permanent seed prostate brachytherapy

Abstract: PurposeWe examined the influence of body mass index (BMI) and body fat distribution on rectal dose in patients treated with permanent seed brachytherapy for localized prostate cancer.Methods and materialsWe analyzed 213 patients treated with I125 seed brachytherapy for localized prostate cancer. BMI and rectal dosimetry data for all patients were available. Data on visceral and subcutaneous fat distribution at the level of the iliac crest (n = 140) as well as the distribution of periprostatic and subcutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
5
3
Order By: Relevance
“…Similar observations were reported by Tiberi et al. , who defined PPAT as the contour at the level of the superior border of the symphysis pubis with exclusion of the tissue medial to the levator ani muscles on both the anterior and posterior aspects of the CT image, and van Roermund et al. , who defined PPAT in a transverse section at the level of the caput femoris and greater trochanter of the femur.…”
Section: Relationships Between Peri‐prostatic Adipose Tissue and Prossupporting
confidence: 76%
See 1 more Smart Citation
“…Similar observations were reported by Tiberi et al. , who defined PPAT as the contour at the level of the superior border of the symphysis pubis with exclusion of the tissue medial to the levator ani muscles on both the anterior and posterior aspects of the CT image, and van Roermund et al. , who defined PPAT in a transverse section at the level of the caput femoris and greater trochanter of the femur.…”
Section: Relationships Between Peri‐prostatic Adipose Tissue and Prossupporting
confidence: 76%
“…The accumulated weight of evidence to date supports an association between PPAT quantity and increased PCa aggressiveness, although the mechanistic basis of this association remains inconclusive and has limited the development of potential interventions. Measuring PPAT area or density showed more significant correlations with PCa aggressiveness than measuring general obesity markers BMI and waist circumference , while the correlation of PPAT thickness with BMI or weight was non‐significant or weak . Moreover, no association has been demonstrated between subcutaneous adipose thickness and PCa aggressiveness ; thus, PPAT measurements may serve as an independent predictor of PCa aggressiveness rather than as a surrogate measure for body adiposity.…”
Section: Discussionmentioning
confidence: 88%
“…This is contrary to our previous publication (Tiberi et al, 2014), where our group was able to show a weak correlation between BMI, VAT, SAT and PPAT. Additionally, we found that PPAT is independent of BMI, compared to the volume and density of VAT and SAT which were correlated with BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we found that PPAT is independent of BMI, compared to the volume and density of VAT and SAT which were correlated with BMI. This is contrary to our previous publication (Tiberi et al, 2014), where our group was able to show a weak correlation between BMI, VAT, SAT and PPAT. This could be because of the fact that the PPAT was defined differently in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Tiberi et al . also found a negative correlation between BMI and dose to the rectum [23]. In addition to affecting rectal dose, we suggest that prostate-rectum interface adipose tissue can also have a negative effect on the anterior dose received by the prostate.…”
Section: Discussionmentioning
confidence: 54%